Analisis Efektivitas Mesin Tette 3200 Line 1 Guna Meminimalisir Waktu Downtime Dengan Metode Overall Equipment Effectiveness di PT. BI - Hermanto, Hermanto; Wiratmani, Elfitra; Irvan, M. (Metris: Jurnal Sains dan Teknologi, 2017)
Overall Equipment Effectiviness (OEE) is one of the way to determine the level of effectiveness of utilization of equipment. OEE is known as an application program from Total Preventive Maintenance (TPM). This study measured OEE is a performance value that is 52.84%. The study found that speed losses is one of the real issues, namely the value of idle and minor STOPPAGE i.e. 42.01% and this loss occurs due to several reasons such as waiting for the materials in the process and not the operator, so the recommended action is to strengthen supervision of employees, mainly machine operators. After doing research, calculating and analyzing the value of Overall Equipment Effectiveness of engine performance fette 3200 line 1, the factors that cause OEE values below the standard affected the performance score is 52.84%, the value of availability is 79.48%, the value of quality that is 97.89% for roots cause of the low value of OEE that occurred in PT. Bayer Indonesia in 3200 fette production line machine line 1 in the period January-September 2015 caused availability value, value performance, quality and value are still below standard OEE is 85%. Difference OEE values obtained under the standard is 41.04%. Propose strategies with the engine Fette 3200 to increase the value of OEE in order to suppress the downtime by pursuing a strategy of monitoring the machine operator so that the operator can do the job effectively, create standard ways of cleaning and setup time machine that not a lot of time discarded, do make to stock to part critical components so that no downtime high value.